DESIGN OF HIGH GAIN MULTISTAGE AMPLIFIER - Mr Sudhir Dakey,; Mr Madhira Eswar Viswanath, (Utilitas Mathematica, 2025)
Due to deteriorating devices and circuit performance as well as an increase in short channel non-ideal effects, analog design remains difficult for designers at lower technological nodes. Medical data collecting and signal processing often require a high gain, low noise amplifier. Because CMOS differential amplifiers have excellent gain, bandwidth, phase margin, and power consumption, they are a good option for designers. The gain and performance are further enhanced by many amplifier stages. As the number of transistors increases, the total gain is likewise improved by many stages of PMOS load. With a greater W/L ratio of PMOS at the output stage amplifier, self-bias operational transconductance amplifiers are a good option for achieving high gain. Using LT SPICE, high gain self-bias double-stage and triple-stage CMOS-based amplifiers were built at the 45nm technology node. To choose the best amplifier architecture and circuit design, performance evaluation is done using AC and transient analysis.